PENGARUH PROGRAM 86 NET TV TERHADAP SIKAP PENONTON - Ardoyo, Novalia Agung Wardjito (Universitas Prof. Dr. Moestopo (Beragama), 2018)
From several reality show programs in Indonesian television, there was 86 program on NET TV. Almost 3 years this program broadcast, and describe some story about Indonesian Police activity. From AC Nielsen index, 86 has a rating value 1,2% and share 4,9%. This means that the program still has many viewers (audience). This paper will argue that delivering such news in such a way by mass media especially television has the ability to shift attitude of the large audience simultaneously. The element of program success theory from Morissan will be used together with a quantitative approach, and survey through stratified sampling among the residents of Cipulir. It was found that the Impact 86 NET TV toward audience attitude is has 45,7% possitive effect.